Risk Mitigation Via Integrating House of Risk and Probability Impact Matrix in Halal Food Supply Chain - Fitra Lestari; Ahmad Mas’ari; Silfia Meilani; Irsan Nuari Riandika; Abu Bakar Abdul Hamid (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
One of the food industry challenges is how to identify sources of risk by considering the halal concept. This study aimed to identify risks and determine risk handling priorities in the supply chain strategy of halal food. This research offered integration of the house of risk and the probability impact matrix to manage risk mitigation in the halal food industry. A case study in the halal food industry was applied in Indonesia based on Supply Chain Operations Reference (SCOR). This study identified 27 risk events and 31 risk agents through 2 phases. Result research showed that employees who did not have special skills (A20) had the highest risk. Moreover, reward and punishment to employees (PA16) was the best proactive action for making effective improvements. The implication of this research is to provide recommendations to management in mitigating risks in the halal food industry.